2019
DOI: 10.1891/1061-3749.27.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Tool for the Assessment of Nurses' Attitudes Toward Delirium

Abstract: Background and PurposeThe prevalence of delirium during hospitalization is high in older patients and there is evidence of staff regarding them as unpopular or a burden. This study aims to develop an instrument examining nurses' attitudes toward patients with delirium.MethodsStages included (a) content identification, (b) content development, (c) content critique, (e) pilot study with a test–retest reliability, (f) field study consisting of psychometric testing of the internal consistency and construct validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…These factors are “emotions”, “behavior”, and “beliefs”, corresponding to 37.025%, 12.792%, and 5.652% of the variance respectively. The whole process of the development and validation of the ATOD is presented in a separate publication [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are “emotions”, “behavior”, and “beliefs”, corresponding to 37.025%, 12.792%, and 5.652% of the variance respectively. The whole process of the development and validation of the ATOD is presented in a separate publication [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the questionnaire measuring attitudes, validity and reliability tests were performed [ 32 ]. In addition, for all items, mean values and percentages in each category indicated positive, negative, or neutral attitudes.…”
Section: Methodsmentioning
confidence: 99%
“…10 There is evidence that ICU nurses perceive patients with delirium as adding to their workload, and this may be one of the more negative factors for nurses to evaluate delirium. 26 A study showed that when medical staff use delirium assessment tools to assess delirium, the assessment tools will be less effective than researchers use these tools. 10 A reduction in the effectiveness of assessment tools can reduce the Open access willingness medical staff to perform assessments.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the assessment of SSD still uses delirium assessment tools, so the problems in delirium assessment also affect nurses’ attitudes towards the assessment of SSD 10. There is evidence that ICU nurses perceive patients with delirium as adding to their workload, and this may be one of the more negative factors for nurses to evaluate delirium 26. A study showed that when medical staff use delirium assessment tools to assess delirium, the assessment tools will be less effective than researchers use these tools 10.…”
Section: Discussionmentioning
confidence: 99%